A Survey of Preclinical Studies Evaluating Nanoparticle-Based Vaccines Against Non-Viral Sexually Transmitted Infections - Abisoye-Ogunniyan, Abisola; Carrano, Isabella M.; Weilhammer, Dina R.; Gilmore, Sean F.; Fischer, Nicholas O.; Pal, Sukumar; de la Maza, Luis M.; Coleman, Matthew A.; Rasley, Amy (Frontiers in Pharmacology, 2021)
A worldwide estimate of over one million STIs are acquired daily and there is a desperate need for effective preventive as well as therapeutic measures to curtail this global health burden. Vaccines have been the most effective means for the control and potential eradication of infectious diseases; however, the development of vaccines against STIs has been a daunting task requiring extensive research for the development of safe and efficacious formulations. Nanoparticle-based vaccines represent a promising platform as they offer benefits such as targeted antigen presentation and delivery, co-localized antigen-adjuvant combinations for enhanced immunogenicity, and can be designed to be biologically inert. Here we discuss promising types of nanoparticles along with outcomes from nanoparticle-based vaccine preclinical studies against non-viral STIs including chlamydia, syphilis, gonorrhea, and recommendations for future nanoparticle-based vaccines against STIs.